Gra w Orwella - Kłosiński, Michał (Przestrzenie Teorii, 2019)
The article presents an interpretation of Orwell video games in context of available analytical tropes in Orwellian research. The paper touches on various problems described by academic readers of Nineteen Eighty-Four and tries to answer the question whether games provide innovations in the way they problematize socio-political issues in comparison to Orwell’s classic novel. In the introductory part, the author discusses the possibility of utilizing the notion of critical dystopia in the analysis of Orwell video games. The following chapters touch on the subject of cultural references, realistic styles, biopolitics and class representations.